Problems of the works of F.Sagan in the translation of the works into Uzbek - Dilnoza T.Mazlitdinova (International Journal of Advanced Science and Technology, 2020)
This given article is about the recreation of moral problems of the original in literary translation. The Russian variant of Françoise Sagan’s novel “Sunlight on cold water” by N.Nemchinova and its Uzbek translation by A.Sharafiddinovare analyzed.